International development issues and challenges - Kingsbury, Damien; McKay, John; Hunt, Janet; McGillivray, Mark; Clarke, Matthew (Houndmills, Basingstoke, Hampshire Palgrave Macmillan, 2012)
"This text provides a critical interdisciplinary introduction to the theory, practice and study of development. The thoroughly revised and updated new edition takes account of the impact of the global financial crisis, the economic rise of China and India and the further ramifications of global warming"--Provided by publisher.
Introduction -- 1. What is development? / Mark McGillivray -- 2. Reassessing development theory / John McKay -- 3. Aid and development / Janet Hunt -- 4. Globalization and development / Damien Kingbury -- 5. The economics of development / John McKay -- 6. Continuing crises: the developing world and the global financial crisis / John McKay -- 7. Politics, governance and development / Damien Kingsbury -- 8. Poverty alleviation and development / Matthew Clarke -- 9. Community development / Damien Kingsbury -- 10. Gender and development / Janet Hunt -- 11. Environment and development / Damien Kingsbury -- 12. Terrorism, Violence and Development / John McKay.
Previous edition entered under title.
Keywords: Poverty -- Developing countries; Economic assistance -- Developing countries; Economic development -- Developing countries; Globalization -- Economic aspects -- Developing countries; Developing countries -- Economic conditions